Manifestações matemáticas interpretadas no processo da construção de casas utilizando o adobe: um estudo a partir da etnomodelagem - Jesus, Márcio Junior Pereira de (Universidade Federal do Tocantins, 2023)
The study was theoretically based on Etonomodeling to understand the adobe construction process and also their use in the construction of houses made by the residents of the Sapé-Arraias-TO community. The research problem that guided this research was to know “what way can you work the objects of knowledge of Mathematics from the mathematical manifestations found in the process of building houses with adobe?” The reasons that led me to develop this research are in my practical experiences, both as a son of residents of this community and as a future Mathematics teacher. The general objective of this study was to perceive, from the process of building houses with adobe, mathematical manifestations that can be considered starting points to build sequences of activities to use them in Mathematics classes in Basic Education. Data collection was carried out through interviews with residents about house construction, for which a channel was created on the youtube platform, in which students signed up to learn step by step how to make adobe. The results showed the existence of ethnomathematical practices in the construction of houses and from the interpretation of these mathematical manifestations, based on ethnomodeling, sequences of activities were built that allowed the dialogue of popular knowledge with the objects of knowledge of school mathematics in basic education.